The Effect of the Peer Feedback Technique on Students’ Writing Ability in Recount Text - Anggraini, Lydia Putri; Huda, Tanzil; Oktarini, Widya (Journal of English Language and Education, 2023)
This study aims to know the effect of the use peer feedback technique on students' writing ability in recount texts. A quasi-experimental design was employed, involving eleventh-grade students from SMA Muhammadiyah 3 Jember. The sample consisted of two classes: Class XI Bahasa as the experimental group and Class XI IPA 3 as the control group, comprising a total of 42 students. Data collection was conducted through a written test. The findings indicated that the average pre-test score for the experimental class was 79.32, while the average post-test score was 89.58. The results of the independent sample t-test analysis revealed a Sig. (2-tailed) value of 0.000, which is less than the predetermined significance level of 0.05. Consequently, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. These findings indicate a significant effect of using the peer feedback technique on students' writing ability in recount texts.